Transcriptomic analysis of humic acid in relieving the inhibitory effect of high nitrogen on soybean nodulation - Zhang, Wenhua; Li, Jia; Li, Hongya; Zhang, Dongdong; Zhu, Baocheng; Yuan, Hongli; Gao, Tongguo (Frontiers in Plant Science, 2023)
Nitrogen fertilizer intake promotes soybean growth before the formation of nodules, but excess nitrogen has an inhibitory effect on soybean nodulation. It is important to balance nitrogen levels to meet both growth and nodulation needs. This study aimed to relieve the inhibitory effect of humic acid (HA) on soybean nodulation under high-nitrogen conditions, and transcriptomic analysis was performed to understand the mechanism. The results showed that a lower level of nitrogen with 36.4 mg urea per pot could increase the number of nodules of soybean, and a higher level of nitrogen with 145.9 mg urea per pot (U4 group) had the best growth indicators but inhibited nodulation significantly. HA relieved the inhibitory effect, and the number of nodules increased by 122.1% when 1.29 g HA was added (H2 group) compared with the U4 group. The transcriptome analysis showed 2995 differentially expressed genes (DEGs) on the 25th day, accounting for 6.678% of the total annotation genes (44,848) under the test conditions. These DEGs were enriched in mitogen-activated protein kinase signaling pathway-plant, flavonoid biosynthesis, and plant hormone signal transduction based on the –log10 (Padjusted) value in the Kyoto Encyclopedia of Genes and Genomes pathway. HA can be used to balance the nitrogen level in soybean planting to control the number of nodules.